Validation of the educational effectiveness of a mobile learning app to improve knowledge about MR image quality optimisation and artefact reduction - Walaa Alsharif; Michaela Davis; Louise Rainford; Andrea Cradock; Allison McGee (Insights into Imaging, 2018)
Abstract Aim The aim was to design an app-based eLearning tool to provide radiographers with information about the physical basis of MR artefacts and practical elimination or/and minimisation strategies to optimise image quality, and to evaluate the impact of a smartphone app on radiographers’ knowledge. Methods The study used the comparison-experimental approach (pre- and post-test). Thirty-five MR radiographers independently reviewed a prepared series of MR images (n = 25). The participants were requested to identify image quality related errors, to specify error-correction strategies and to score how confident they were in their responses. Participants were then divided into experimental (n = 19) and control cohorts (n = 16). The app was provided to the experimental cohort for 3 months; after this period both cohorts re-reviewed the MR image datasets and repeated their identification of image quality errors. Results The results showed a statistically significant difference between control and experimental cohorts relative to participants’ pre- to post-test knowledge level. For the experimental cohort, years of experience, qualification and type of hospital were not associated with radiographer knowledge level and confidence in recognising the presence of an image quality error, naming the error and specifying appropriate correction strategies (p > 0.05). Conclusion The study identified the potential of the smartphone app as an effective educational tool to support MR radiographers’ knowledge in recognising and characterising MR image quality errors. Key Points • A high level of knowledge to optimise MR image quality is crucial. • Ongoing education in image quality optimisation is required. • The potential role of app as an effective educational tool is identified.